Failure study on tensile strength of fiberglass reinforced polymeric composite laminates - رومية , هبة; لطيفة الحموي; محمد خير محمد (Latakia University Journal -Engineering Sciences Series, 2023)
In this paper, the failure of polymeric composite laminates made of unsaturated polyester reinforced with glass fibers was studied when loading on tensile to failure, for different types of glass fibers in order to extrapolate the values ​​of tensile loads to failure and to study the deformation and failure patterns that occur. To achieve this goal, a group of samples was prepared from unsaturated polyester material as a polymeric basis and glass fiber as a reinforcement material, where three types of fibers were used (Mat, Mesh, Unidirectional Fiberglass), and these samples were subjected to a tensile test. Experimental results showed that samples reinforced with oriented glass fibers are more bearing for tensile forces than plates with random fibers, also thickness of samples effect on values and form of failure. Samples upon collapse recorded different and complex patterns of damage and deformation, which increase with the number of layers and vary according to the type of fiberglass used. The experimental results were verified programmatically using Matlab